ORGANISASI FRONT PEMBELA ISLAM DI PEKANBARU - Sediasih, Ifa; Tantoro, Swis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The progress of Muslims in Indonesia can not be separated from the role of Islamic figures and organizations actively conducting business charity activities. An organization must have a good image and behavior in the community and face a variety of practices that are considered incompatible with the values to Islaman that plague the middle of the life of the community. Islamic Defenders Front as a community organization that put Islamic values as the main motivation in doing activities including in the case of da'wah. The purpose of this research is to know the characteristics of the Organization members of the Islamic Defenders Front and the role of the Organization of the Islamic Defenders Front. The research method used is descriptive quantitative by displaying data that has been obtained in tables. The research was conducted at the headquarters of the Islamic Defenders Front of Tanjung Rhu Subdistrict, Limapuluh Pekanbaru Subdistrict. From the result of the research, it is found that the activity of the organization of Islamic Defenders Front that has been planned to be done optimally is seen from the high member activity level.Keywords: Characteristics, Role, Organization